2016
DOI: 10.1371/journal.pone.0164276
|View full text |Cite
|
Sign up to set email alerts
|

Placental Growth Factor (PlGF) in Women with Suspected Pre-Eclampsia Prior to 35 Weeks’ Gestation: A Budget Impact Analysis

Abstract: ObjectiveTo model the resource implications of placental growth factor (PlGF) testing in women with suspected pre-eclampsia prior to 35 weeks’ gestation as part of a management algorithm, compared with current practice.MethodsData on resource use from 132 women with suspected pre-eclampsia prior to 35 weeks’ gestation, enrolled in a prospective observational cohort study evaluating PlGF measurement within antenatal assessment units within two UK consultant-led maternity units was extracted by case note review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
(17 reference statements)
0
17
0
1
Order By: Relevance
“…Hemodynamic‐guided antihypertensive therapy for pregnant women presenting with any type of hypertension significantly reduced the rates of severe maternal hypertension from 18% to 3.5%, when compared with standard care 30. Early detection and characterization of hypertensive disorders of pregnancy should also be investigated from a cost‐savings perspective, as maternal cardiovascular and circulating protein information could impact decision making and disease trajectory 31, 32. From a feasibility perspective, commercial non‐invasive hemodynamic monitoring systems are now available for the convenient and safe monitoring maternal hemodynamics in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic‐guided antihypertensive therapy for pregnant women presenting with any type of hypertension significantly reduced the rates of severe maternal hypertension from 18% to 3.5%, when compared with standard care 30. Early detection and characterization of hypertensive disorders of pregnancy should also be investigated from a cost‐savings perspective, as maternal cardiovascular and circulating protein information could impact decision making and disease trajectory 31, 32. From a feasibility perspective, commercial non‐invasive hemodynamic monitoring systems are now available for the convenient and safe monitoring maternal hemodynamics in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Duckworth and colleagues estimated that inclusion of PlGF in a clinical algorithm for suspected PE could save a mean of UK£582 (€654) per woman tested, via reduced resource use . The algorithm categorizes patients into care levels according to BP and a PlGF cutoff (traffic light) system.…”
Section: Predictive Tests Utilizing Angiogenic Factorsmentioning
confidence: 99%
“…However, the use of angiogenic factors in high‐risk populations (women who present with signs or symptoms of PE) may confer significant economic benefit . Various studies have suggested savings using the sFlt‐1/PlGF ratio of £334/patient (UK), £945/patient (UK); €670/patient (Italy), and using PlGF alone of £35 087/1000 patients (UK) …”
Section: Economic Modelling/potential Economic Impactmentioning
confidence: 99%